Encyclopedia of Life Sciences 2012
DOI: 10.1002/9780470015902.a0003365.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Farming in Plants

Abstract: The commonly used term ‘molecular farming’ describes the large‐scale production of valuable proteins in transgenic plants, including antibodies, vaccines, other pharmaceuticals and industrial proteins. Compared to traditionally used systems such as microbial cultures, plants offer many advantages with respect to economy, quality and safety. Especially attractive is the possibility to power protein production using natural sunlight and atmospheric carbon dioxide. Furthermore, transient expression systems offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…125 It was shown that the amount secured should be higher than 1% of soluble protein to make it commercially interesting. 212 In contrast to animal and microbial expression systems, transgenic plants have several advantages in terms of safety, cost and ease of production for fabricating therapeutic biomolecules. However, there are quite a few challenges, such as public acceptance, transgene escape, biosecurity, and public reception among others, but it is anticipated that in not too distant future, molecular farming will see substantial accomplishments with the precise and technical inquiries; significant concerns are summarized in Figure 5.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…125 It was shown that the amount secured should be higher than 1% of soluble protein to make it commercially interesting. 212 In contrast to animal and microbial expression systems, transgenic plants have several advantages in terms of safety, cost and ease of production for fabricating therapeutic biomolecules. However, there are quite a few challenges, such as public acceptance, transgene escape, biosecurity, and public reception among others, but it is anticipated that in not too distant future, molecular farming will see substantial accomplishments with the precise and technical inquiries; significant concerns are summarized in Figure 5.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Genetically modified (GM) plants with moderate resistance to pathogenic bacteria and fungi have been developed by expressing AMPs either constitutively or induced by pathogens (reviewed by Marcos et al, 2008;Montesinos, 2007). Many different recombinant proteins have been expressed in plants (Fischer et al, 2004;Hoja and Sonnewald, 2013;Twyman et al, 2003), and the applications envisaged for CECMEL11 peptides suggest that plant-based expression would be preferable, to develop plants either that are disease resistant or that express AMPs for medical and industrial applications. Large-scale chemical synthesis of peptides above around six amino acids is only economically viable for applications of very high added value.…”
Section: Introductionmentioning
confidence: 99%